Risk Assessment for Sudden Death in Epilepsy: The SUDEP-7 Inventory - Novak, Jennifer L.; Miller, Patrick R.; Markovic, Daniela; Meymandi, Sheba K.; DeGiorgio, Christopher M. (Frontiers in Neurology, 2015)
Background: Sudden Unexpected Death in Epilepsy (SUDEP) is a major cause of death in those with drug resistant epilepsy. There is a need for inventories and biomarkers associated with the risk for SUDEP. Objective: To explore the revised SUDEP Risk Inventory (SUDEP-7) in a cohort with Drug Resistant Epilepsy, and determine the association with Heart Rate and other covariates. Methods: 25 subjects with severe drug-resistant epilepsy were enrolled in a clinical trial for epilepsy. Baseline demographics, duration of epilepsy, seizure types, seizure frequency, seizure severity, AED’s, and vital signs were collected. Heart rate variability (HRV) was calculated from 1-hour recordings of ECG. A SUDEP Risk Inventory (SUDEP-7) was administered, which included 7 validated and weighted risk factors initially identified by Walczak et al. as factors associated with SUDEP risk. Results: The total score on the revised SUDEP-7 ranged from 1 to 7, mean = 3.4 (sd 1.8). The SUDEP Risk Inventory score was inversely correlated with RMSSD (Pearson r= -0.45, P=0.027). The following variables were significantly associated with RMSSD: epilepsy duration (p=0.02), age (p=0.03), and developmental intellectual disability (p<0.001). The correlation between RMSSD and SUDEP 7 tended to persist also after the adjustment for patient age (r = -0.40, p=0.05). Two subjects died of SUDEP: their SUDEP-7 scores were above average and in the upper 25 and 50th percentiles respectively (6 and 4, mean = 3.4) Conclusions: RMSSD, a measure of low frequency heart rate variability, was significantly associated with SUDEP Risk Inventory (SUDEP-7) scores. Using a multivariable model, the covariates of developmental intellectual disability, age, and duration of epilepsy were also significantly associated with decreased HRV. The correlation between decreased HRV and a higher SUDEP-7 score remained unchanged even after the adjustment for patient age. The results suggest that older age, greater duration of epilepsy and the presence of developmental intellectual disability may increase the risk of SUDEP through their direct influence on decreasing the vagus nerve mediated HRV.